The population growth and the nutritional status of Moina macrocopa feed with rice bran and cassava bran suspensions - Ahmad Shofy Mubarak; Dedi Jusadi; Muhammad Zairin Junior; Muhammad Agus Suprayudi (Jurnal Akuakultur Indonesia)
ABSTRACT